THE IMPACT OF PERSONALITY, FINANCIAL INCENTIVES, AND WORK ENVIRONMENT FACTORS ON ACCOUNTING STUDENTS’ INTEREST IN PURSUING A CAREER IN INTERNAL AUDITING - Angel Yuliyanti Siburian; Vinny Stephanie Hidayat (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2025)
The purpose of this study is to examine how work environment, financial incentives, and personality affect interest in a career as an internal auditor. All of the participants in this study were Maranatha Christian University students enrolled in the Accounting Study Program. Explanatory research is the methodology employed in this study. The sample strategy employed was purposeful sampling. Thirty-eight respondents were selected from the circulated questionnaires, and they served as research samples. SPSS was used to process the data. The T-test and F-Test or multiple linear regression analysis, was employed as a technique for assessing hypotheses. According to the study's findings, career interest as an internal auditor was not impacted by the work environment, but it was influenced by personality and financial rewards.